Factors which influence death rates in different types of epidermal necrolysis (drug reactions). (1st April 2020) - Traikia, C.; Hua, C.; Le Cleach, L.; de Prost, N.; Hemery, F.; Bettuzzi, T.; Chosidow, O.; Wolkenstein, P.; Ingen‐Housz‐Oro, S.; Sbidian, E.
Summary: Toxic epidermal necrolysis (also called TEN or Lyell syndrome) is a devastating type of drug allergy. It affects only one or two people per million, but is often fatal. Patients rapidly lose more than 30% of their skin (known as skin detachment) and suffer blistering of membranes such as eyes, mouth and genitals. Stevens–Johnson syndrome (SJS) is similar but with less than 10% skin detachment and the term SJS/TEN overlap syndrome refers to those with 10‐29% skin detachment. We know that patients who are older with more detached skin and other illnesses are more likely to die, but we don't know whether the death rate also depends on where they are treated. Management (medical care) of these conditions is very complex involving many different specialties, such as dermatology, ophthalmology and oral medicine, and few hospitals treat enough patients to gain expertise. This study uses national data on patients aged over 15 years, treated in French hospitals over a five year period from January 2010. Of 991 patients seen in 300 hospitals, 60% had SJS, 17% had SJS/TEN overlap and 23% had TEN. In total, 109 (11%) patients died: nine (2%) with SJS, 26 (15%) with SJS/TEN overlap and 74 (33%) with TEN. The number of cases per hospital over five years ranged from one to more than 70, and survival rate was significantly better for hospitals with more cases. Being transferred between hospitals did not affect the death rate. The authors conclude that patients with SJS and TEN should be transferred to centres with more experience in managing these conditions. This is a summary of the study: Individual‐ and hospital‐level factors associated with epidermal necrolysis mortality: a nationwide multilevel study, France, 2012–2016